Small business survival book : - Weltman, Barbara (John Wiley & Sons, 2006)
Owning a small business can be a fulfilling and financially rewarding experience, but to be successful, you must know what to do before starting a business; what to do while the business is up and running; and, most importantly, what to do when the business runs into trouble. With a combined fifty years of small business experience between them, authors Barbara Weltman and Jerry Silberman know what it takes to make it in this competitive environment, and in Small Business Survival Book, they show you how. In a clear and concise voice, Weltman and Silberman reveal twelve surefire ways to help your small business survive and thrive in today's market. With this book as your guide, you'll discover how to: Delegate effectively, monitor cash flow...